Design and Construction of Mechanical Equipment Coffee Roasters Rotary Type A - Wawan Ginting; Achwil Putra Munir; Adian Rindang; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Roasting is an important step in the production of coffee powder, wherein the formation of aroma and distinctive flavor of coffee is determined at this stage. Of the national production of coffee beans, only 20% are processed and marketed in the form of secondary products such as roasted coffee, ground coffee and instant coffee. This study was plan to build a rotary mechanical device of coffee roasters. The study was conducted with literature study, experiment, observation and testing of the tool. The parameters measured were the effective capacity of the tool. The results showed that the effective capacity of the coffee roasters was 2.151 kg.hour-1. Key words: postharvest equipment, coffee, roasting, effective capacity.